Apparent Molal Volumes and Partial Molar Volumes of Aqueous Solutions of Some Biologically Important Compounds at 308 and 318 K - Sahaya Amutha, P.; Rosario Rajkumar, X. (Asian Journal of Chemistry, 2010)
Apparent molal volumes (ϕv), partial molar volumes (ϕv 0) of aqueous solutions of seven biologically important compounds [glucose, sucrose, urea, citric acid, tartaric acid, ascorbic acid and oxalic acid] in different molality [0.1-1.0 mol/kg] at two different temperatures [308 and 318 K] have been determined. For density measurements sprengel and Ostwald pyknometer has been used. Partial molar volumes (ϕv 0) at infinite dilution have been obtained from ϕv values using the Masson equation. ϕv 0 values are positive for all the compounds studied and apparent molal volumes increase with increase in concentration of ascorbic acid. It decreases with increase in concentrations of other compounds [glucose, sucrose citric acid, tartaric acid and oxalic acid]. Variations in ϕv values with change in solute concentrations are discussed in terms of solutesolvent interactions and electrostriction.